Intelligent network Services Based ECG Signal Monitoring - Sumathi, M.; Sushita, K.; Shanmugasundaram, N.; N.Ganesh, E. (International Journal of Engineering and Technology, 2018)
The technology and the nature of the Telecom environment are changing rapidly. Network Operators and service Subscribers have to differentiate themselves from the competitors to keep their market shares and to attack new market segments. One way of differentiating and of increasing revenues is to host IN (Intelligent Network) services that target market segments that usually were not in the operatorsâ€™ focus. In the current paper, such a service is presented, service that is related to the medical tele-monitoring. The paper is presenting a part of the technical aspects and market perspectives specific to such a service.Â Â